2016
DOI: 10.1503/jpn.140220
|View full text |Cite
|
Sign up to set email alerts
|

Healthy co-twins of patients with affective disorders show reduced risk-related activation of the insula during a monetary gambling task

Abstract: IntroductionHeritable genetic traits and environmental components both contribute to the etiology of affective disorders. While the specific contribution of these 2 factors to disorder onset remains elusive, family and twin studies have consistently identified a family history of affective disorders as a major risk factor.1 First-degree relatives of patients with depression have a 2-fold to 4-fold increased risk for depression than individuals with no psychiatric history in first-degree relatives.2 Yet the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…In the present study, we found a significant effect of risk level during the decision phase upon activity in the anterior insula: higher-risk choice led to increased activity. It has been frequently suggested that the anterior insula is relevant for higherlevel processing 42 and risk level, 43 as a consequence of its involvement in learning the negative value of loss-prediction cues. 44,45 Activation of the posterior insula has also been associated with lower risk levels, suggesting that different divisions of the insula play opposing roles during risk processing.…”
Section: Healthy Controls Ocdmentioning
confidence: 99%
“…In the present study, we found a significant effect of risk level during the decision phase upon activity in the anterior insula: higher-risk choice led to increased activity. It has been frequently suggested that the anterior insula is relevant for higherlevel processing 42 and risk level, 43 as a consequence of its involvement in learning the negative value of loss-prediction cues. 44,45 Activation of the posterior insula has also been associated with lower risk levels, suggesting that different divisions of the insula play opposing roles during risk processing.…”
Section: Healthy Controls Ocdmentioning
confidence: 99%
“…Converging neurobiological and behavioral evidence has attributed these symptoms to deficits in discrete reward-related processes, including reduction of attentional bias toward positive stimuli (Joormann & Gotlib, 2007), of positive affect in response to pleasant stimuli (Berenbaum & Oltmanns, 1992), and of reward responsiveness (Pizzagalli, Iosifescu, Hallett, Ratner, & Fava, 2008). The available neuroimaging data have revealed numerous functional and structural changes in the neural system subserving these processes in both patients with UD and BD (Bracht, Linden, & Keedwell, 2015;Diener et al, 2012;Hamilton, Chen, & Gotlib, 2013;Houenou et al, 2011;Wise et al, 2017) and never-depressed first-degree relatives (Macoveanu et al, 2014(Macoveanu et al, , 2016a(Macoveanu et al, , 2016b(Macoveanu et al, , 2018Olino et al, 2014;Singh et al, 2014). However, it remains unclear how distinct components of reward processing are affected in UD and BD and whether or not some of these changes are also present in unaffected relatives who are at increased risk for mood disorders (Oquendo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, two randomized placebo-controlled trials from our group revealed that eight weekly EPO infusions improved several cognitive domains in patients with BD and TRD [ 39 , 40 ]. This was accompanied by increased activity in dlPFC and dorsomedial PFC (dmPFC) during working memory and episodic encoding tasks [ 44 , 45 ]. Notably, a single dose of EPO enhances cognition-related dlPFC and dmPFC activity without producing any change in red blood cells [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%